2006
DOI: 10.1111/j.1540-8159.2006.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Initiation Pattern of Polymorphic Ventricular Tachycardia in Patients with Implantable Cardioverter Defibrillators

Abstract: The stored ICEGs demonstrate that PVT is most often preceded by ventricular ectopy. To be reverted, nonsudden onset episodes require higher levels of shock energy and more frequently multiple shock achievements than sudden onset episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…Our findings of a shorter PI of the first beat that initiates the arrhythmia and slower heart rate preceding PVTs of nonsudden onset are in accordance with a previous study (22) on characteristics of PVT initiation in patients who underwent ICD implantation. Taylor et al (20) demonstrated that PVTs, in comparison with MVTs, had shorter PIs and were preceded by bradycardia, postulating that the triggered mechanism may be responsible for a shorter PI in PVTs.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our findings of a shorter PI of the first beat that initiates the arrhythmia and slower heart rate preceding PVTs of nonsudden onset are in accordance with a previous study (22) on characteristics of PVT initiation in patients who underwent ICD implantation. Taylor et al (20) demonstrated that PVTs, in comparison with MVTs, had shorter PIs and were preceded by bradycardia, postulating that the triggered mechanism may be responsible for a shorter PI in PVTs.…”
Section: Discussionsupporting
confidence: 81%
“…Most studies described patterns of monomorphic VT onset in patients with coronary artery disease, Chagas disease and ischemic or nonischemic cardiomyopathy with an ICD (2)(3)(4)(19)(20)(21)(22). Our study complements the results of previous reports by characterizing patterns of PVT initiation early after acute MI.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Eventually, at the end of the nineties, it has been shown that coronary artery disease (CAD) and dilated cardiomyopathy (DCM) underlie different mechanisms of spontaneous and induced VT [Pogwizd et al 1998, Chung et al 1997; moreover ,differences in spontaneous VT from ICD recipients began to be investigated. Indeed, since the early 2000, various studies have analyzed intracardiac electrograms (EGMs) and initiation VT pattern [Gorenek et al 2006, Taylor et al 2000, Saeed et al 2000, while others have investigated circadian distribution [Carson et al 2000, Englund et al 1999, Eksik et al 2007, Taneda et al 2001] of spontaneous VT in ICD patients. Some of these studies [Taylor et al 2000, Saeed et al 2000, Englund et al 1999] have failed to detect differences in both the patterns of initiation and in EGMs between patients with different etiologies of heart disease.…”
Section: Introductionmentioning
confidence: 99%